The CRITICAL ANALYSIS OF MARRIAGE DISPENSATION DUE TO ZINA: GENDER, CHILD PROTECTION, AND ISLAMIC LAW PERSPECTIVES IN INDONESIA - Anisa, Lina Nur (Al Maqashidi : Jurnal Hukum Islam Nusantara, 2025)
This study critically examines the practice of marriage dispensation due to zina (premarital pregnancy) in Indonesia through the integrated perspectives of gender justice, child protection, and Islamic law. Although Law No. 16 of 2019 raised the minimum age of marriage to strengthen child protection, empirical data show a continued increase in marriage dispensation applications and approvals in the Religious Courts, particularly in cases involving premarital pregnancy. Existing studies largely address marriage dispensation from doctrinal Islamic law or child marriage policy perspectives, while critical analyses of how judicial discretion operates in practice remain limited. The novelty of this study lies in its reconceptualization of judicial discretion as a mechanism of moral mediation rather than a rights-protective safeguard, and in its demonstration of how moral narratives surrounding zina shape judicial reasoning and marginalize child-centered assessments. Using a qualitative library-based method with a critical socio-legal approach, this study analyzes Religious Court decisions issued between 2019 and 2023, academic literature, and institutional reports. The findings show that marriage dispensation is frequently framed as an immediate response to social stigma and moral anxiety, causing the best interests of the child principle to function symbolically rather than substantively. This study contributes to Islamic family law scholarship by offering a new analytical lens for evaluating marriage dispensation practices and their implications for child protection and gender justice.